Magnetite ferrofluids stabilized by sulfonato-calixarenes - Chin, S.F.; Mohamed, Makha; Raston, Colin L.; Saunders, Martin (Royal Society of Chemistry, 2007)
Magnetite (Fe304) nanoparticles stabilised by sulfonatocalixarene macrocycles are readily accessible by a rapid in situ co-precipitation, and exhibit ferro-fluidic and superparamagnetic behaviour.